Urgensi Implementasi Fundraising Lembaga Amil Zakat Infak, dan Sedekah Nahdlatul Ulama (LAZISNU) Kabupaten Jember dalam Meningkatkan Jumlah Pendapatan Dana di Era Normal Baru - Andriani, Nita; Chotib, Moch.; Rahayu, Nurul Widyawati Islami (Maddah: Journal of Advanced Da'wah Management Research, 2023)
Indonesia is a country with the largest Muslims in the world. The potential for zakat is also great. In Jember itself, which is a barn for NU residents, it has not been able to exploit this potential. During covid-19 economic pandemic has decreased. Fundraising is an urgent matter for LAZISNU Jember. Fundraising are the continuity of the institution. In the new normal period with the right fundraising techniques LAZISNU Jember can increase the amount of fund revenue. This study used qualitative research methods. Data collection techniques by interview, observation and documentation. Research location of the Institute for Zakat, Infaq, and handout Nahdlatul Ulama (LAZISNU), Jember. The results of this study are: 1) The urgency of fundraising at LAZISNU Jember for the sustainability of LAZISNU programs in Jember 2) Implementation of LAZISNU fundraising in Jember using fundraising techniques. Direct fundraising and indirect fundraising and structural strengthening innovation 3) Supporting factors: Great potential because of 26 MWC only 8 MWC were activated, optimization of publications on www.nu.or.id and social media, freedom in managing ZISWAF , and LAZISNU Jember inclusive. While the inhibiting factor: LAZISNU, Jember does not have an official Amil who is paid every month, the impact of the Covid-19 pandemic must follow health protocols, and most people choose to donate directly to mustahik.